Buchnera kisimbai (Orobanchaceae), a new species described from the copper-rich soils of Haut-Katanga in the Democratic Republic of the Congo - Fischer, Eberhard; Ilunga, Edouard Ilunga Wa (Phytotaxa, 2025)
A new species of Buchnera is described from copper-cobalt enriched soils in Katanga, D.R. Congo. The plant we describe as B. kisimbai has been previously misidentified as Buchnera randii. The differences between these species, i.e. the ovate cauline leaves (linear-lanceolate in B. randii), the smaller bracts, the larger calyx, the longer corolla tube, and the larger corolla lobes, are described.